Design and optimization of the scavenging system of a multi-cylinder two-stroke scotch-yoke engine - Ng, Tee Neng (2006)
A two-stroke engine complete with a scavenging system, operating with external pumping mechanism is being developed. The engine comprises of two pair of combustion chambers and a pair of piston pumps that are integrated onto the Scotch-Yoke crank mechanism. The Schnurle type loop scavenging arrangement was selected for the scavenging arrangement for the engine port design. The pump was to be driven by the engineâ€™s pistons linkages. The significant advantages of this opposed piston-driven pump concept is the double action of air pumping at every 180Â° interval of crankshaft revolution. In addition, extensive work using Computational Fluid Dynamic code simulation tools were applied throughout the project to ensure that the scavenging port geometry is optimized. Also developed was a scavenging test rig specifically to verify the simulation results. The unfired tracer gas sampling method was developed for the scavenging measurement purposes. The experimental testing was carried out successfully with the use of instrumentations such as Dewetron High Speed Data Acquisition and crank encoder. Both the simulation results and experimental results showed good scavenging characteristic, where the scavenging efficiency is closed to the perfect mixing scavenging model. The development of the scavenging system will allow for the reduction of the pollutant emission, and the overcome short-circuiting problem of the two-stroke engine